Optimal allocation of distributed generation using a two-stage multi-objective mixed-integer-nonlinear programming - Porkar, S.; Poure, P.; Abbaspour-Tehrani-fard, A.; Saadate, S. (European transactions on electrical power, 2011)
Cost is one of the most essential factors that influence many decisions taken in the distribution system planning. In general, cost can be defined as everything that should be sacrificed to gain the desired results. This paper proposes a new two‐stage methodology for distributed generation (DG) placement as an attractive option for distribution system planner. This method aims to minimize cost and maximize total system benefit (TSB). Optimal placement and size are obtained from total cost minimization mathematical problem which is solved in the first stage. For each DG cost characteristics and for each investment payback time, there is an optimal location and size. Then the optimal DG investment payback time results from the TSB maximization problem, which is solved in the second stage. The various DG technologies offer the opportunity of selecting the right energy solution at the right location. Five types of DG are tested to give system deciders some choices. Different system conditions are simulated to illustrate the effect of DG installation on the distribution system as well as the ability of the proposed methodology. A user‐friendly software package has been developed to solve efficiently and quickly the two optimization mathematical problems. The proposed methodology has been tested on IEEE 30‐bus test system. Copyright © 2010 John Wiley & Sons, Ltd.